Posidonia oceanica (L.) based compost as substrate for potted basil production. (14th October 2014) - Mininni, Carlo; Grassi, Francesco; Traversa, Andreina; Cocozza, Claudio; Parente, Angelo; Miano, Teodoro; Santamaria, Pietro
Abstract BACKGROUND Peat is the main component of growing media but is also a non‐renewable resource; therefore European policy strongly encourages the use of peat alternatives such as compost. Posidonia is a Mediterranean seagrass that produces very conspicuous onshore deposits that can be composted. In this study, a commercial green compost and a Posidonia residue‐based compost were tested in order to assess their potential use as substitutes or complements to peat. RESULTS All macro and micro‐element concentrations of the substrates were positively and significantly related to the percentage of composts in the growing media. Plant grown on peat showed higher content of P, Ca, K, Na, Cu, Mn, Zn and Fe, and a slightly higher biomass production in comparison to compost‐based growing media. In contrast, plants grown on compost‐based substrates showed lower uptake of Cd and Cr than peat. CONCLUSION The results indicate that both composts can be used as a complement to the peat for substrate preparation, especially at a rate of 30%. The Posidonia‐based compost showed better productive results in comparison to the green one. Basil grown on the two compost‐based media showed reduced absorption level of potentially toxic metals in comparison to peat. © 2014 Society of Chemical Industry